Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597115
|View full text |Cite
|
Sign up to set email alerts
|

Do developers discuss design?

Abstract: Design is often raised in the literature as important to attaining various properties and characteristics in a software system. At least for open-source projects, it can be hard to find evidence of ongoing design work in the technical artifacts produced as part of the development. Although developers usually do not produce specific design documents, they do communicate about design in different ways. In this paper, we provide quantitative evidence that developers address design through discussions in commits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 8 publications
(7 reference statements)
0
74
0
Order By: Relevance
“…The only difference is the use of scikit-learn for the classifiers, instead of NLTK. Doing this allowed us to match the results that the original paper [5] obtained.…”
Section: A Strict Replicationmentioning
confidence: 96%
See 3 more Smart Citations
“…The only difference is the use of scikit-learn for the classifiers, instead of NLTK. Doing this allowed us to match the results that the original paper [5] obtained.…”
Section: A Strict Replicationmentioning
confidence: 96%
“…RO1: Our first research objective is to assess, by replication, whether it is possible to accurately label a given natural language discussion as pertaining to software design. We conduct an exact replication of the study of Brunet et al [5]. We also examined, but did not exactly replicate, similar studies (as shown in Table I).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…CSE offers new opportunities to overcome this capture problem since it provides multiple practices and documentation locations in which developers can capture decision knowledge. () For example, developers capture decisions when they commit code in commit messages …”
Section: Foundationsmentioning
confidence: 99%